Stress and lasting symptoms following injury: Results from a 4-month cohort of trauma patients recruited at the emergency department. (January 2020) - Cédric, Gil-Jardiné; Hoareau, Stéphanie; Valdenaire, Guillaume; Contrand, Benjamin; Salmi, Louis-Rachid; Masson, Françoise; Tellier, Eric; Ribéreau-Gayon, Régis; Revel, Philippe; Lagarde, Emmanuel
Highlights: Near 25% of patients admitted in the ED after a minor trauma presented persistent symptoms 3-months after ED treatment. These symptoms are similar to those of post-concussion syndrome. There is a strong association between stress at discharge and occurrence of these symptoms. Intervention could be proposed to reduce stress in the ED and probably prevent the occurrence of Post-concussion like symptoms. Abstract: Introduction: Recent research suggests that up to 20% of minor trauma patients admitted to the emergency department (ED) will suffer from non-specific chronic conditions over the subsequent several months. Thus, the present study assessed the correlates of symptoms that persisted at 4 months after an ED visit and, in particular, evaluated the associations between these symptoms and self-reported stress levels at ED admission and discharge. Method: This study was a prospective observational investigation conducted in the ED of Bordeaux University Hospital that included patients admitted for minor trauma. All participants were contacted by phone 4 months after presentation at the ED to assess the occurrence of post-concussion-like symptoms (PCLS). Results: A total of 193 patients completed the follow-up assessment at 4 months; 5.2% of the participants suffered from post-traumatic stress disorder (PTSD) and 24.5% suffered from PCLS. A multivariate analysis revealed an association between PCLS and stress level at discharge from the ED (odds ratios [OR]: 2.85, 95% confidence interval [CI]: 1.10–7.40). Conclusions: The risk of PCLS at 4 months after an ED visit for a minor injury increased in association with the level of stress at discharge from the ED. These results may improve the quality of life for the millions of patients who experience a stressful injury event every year.